Explaining Africa's (Dis)advantage The Curse of Party Monopoly - Harrison, Ann E. (The World Bank, 2013)
Africa's economic performance has been widely viewed with pessimism. This paper uses firm-level data for 89 countries to examine formal firm performance. Without controls, manufacturing African firms do not perform much worse than firms in other regions. But they do have structural problems, exhibiting much lower export intensity and investment rates. Once the analysis controls for geography and the political and business environment, formal African firms robustly lead in sales growth, total factor productivity levels and productivity growth. Africa's conditional advantage is higher in low-tech than in high-tech manufacturing, and exists in manufacturing but not in services. While geography, infrastructure, and access to finance play an important role in explaining Africa's disadvantage in firm performance, the key factor is party monopoly. The longer a single political party remains in power, the lower are firm productivity levels, growth rates, and sales growth for manufacturing. In contrast, the business environment and firm characteristics (except for foreign investment) do not matter as much. The paper also finds evidence that the effects of the political and business environment are heterogeneous across sectors and firms of various levels of technology